Community and gene composition of a human dental plaque microbiota obtained by metagenomic sequencing - Xie, G.; Chain, P.S.G.; Lo, C.-C.; Liu, K.-L.; Gans, J.; Merritt, J.; Qi, F. (Molecular oral microbiology, 2010)
Summary Human dental plaque is a complex microbial community containing an estimated 700 to 19,000 species/phylotypes. Despite numerous studies analysing species richness in healthy and diseased human subjects, the true genomic composition of the human dental plaque microbiota remains unknown. Here we report a metagenomic analysis of a healthy human plaque sample using a combination of second‐generation sequencing platforms. A total of 860 million base pairs of non‐human sequences were generated. Various analysis tools revealed the presence of 12 well‐characterized phyla, members of the TM‐7 and BRC1 clade, and sequences that could not be classified. Both pathogens and opportunistic pathogens were identified, supporting the ecological plaque hypothesis for oral diseases. Mapping the metagenomic reads to sequenced reference genomes demonstrated that 4% of the reads could be assigned to the sequenced species. Preliminary annotation identified genes belonging to all known functional categories. Interestingly, although 73% of the total assembled contig sequences were predicted to code for proteins, only 51% of them could be assigned a functional role. Furthermore, ∼ 2.8% of the total predicted genes coded for proteins involved in resistance to antibiotics and toxic compounds, suggesting that the oral cavity is an important reservoir for antimicrobial resistance.